VIRTUAL LEARNING ENVIRONMENTS AS A TOOL FOR STUDY OUTSIDE CLASS AND FOR CONTINUING EDUCATION - Denise Costa Dias; Débora Ignácio Alves; Luciana Magnani Fernandes; Lorena Moraes Gueten Gemelli (Universidade Federal do Paraná, 2011)
This is an account of experience with the use of the virtual learning environment (Modular Object-Oriented Dynamic Learning Environment) for carrying out an updating course on techniques of nursing and aspects related to the use of such techniques in clinical situations in health institutions. Professors, health professionals and nursing undergraduates participated in the course. The article presents some reflections on the use of Modular Object-Oriented Dynamic Learning Environment in the teaching-learning process. The comments, posted in forums, highlight the theoretical and practical aspects of this tool and permitted the exchange of experiences and active discussion about the nursing techniques, as much in their formal aspects as in the aspects related to the feelings of those involved in this process of care.